2022
DOI: 10.3390/molecules27134030
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Activity of Nelumbo nucifera Gaertn. Seedpod Extract Attenuated Acetaminophen-Induced Hepatotoxicity

Abstract: The aim is to investigate the effect of lotus (Nelumbo nucifera Gaertn.) seedpod extract (LSE) on acetaminophen (APAP)-induced hepatotoxicity. LSE is rich in polyphenols and has potent antioxidant capacity. APAP is a commonly used analgesic, while APAP overdose is the main reason for drug toxicity in the liver. Until now, there has been no in vitro test of LSE in drug-induced hepatotoxicity responses. LSEs were used to evaluate the effect on APAP-induced cytotoxicity, ROS level, apoptotic rate, and molecule me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…[185] Further seed extract of N. nucifera Gaertn also gives better hepatoprotective and antioxidative activity. [186] This study suggested that the plant extract has the potential to reduce hepatic illness by modulating the signalling pathway, inflammatory factors and reactive oxygen species.…”
Section: In Vivomentioning
confidence: 96%
“…[185] Further seed extract of N. nucifera Gaertn also gives better hepatoprotective and antioxidative activity. [186] This study suggested that the plant extract has the potential to reduce hepatic illness by modulating the signalling pathway, inflammatory factors and reactive oxygen species.…”
Section: In Vivomentioning
confidence: 96%
“…In the present scenario, paracetamol (PC), known as N-acetyl-p-aminophenol (acetaminophen), acts as an analgesic and antipyretic drug, and is highly consumed. Moreover, the overdose of PC drug by humans or experimental animals will result in an increase of oxidative stress that induces lipid peroxidation and causes toxicity to hepatic cells [9]. However, various endogenous resistance mechanisms will operate to scavenge ROS to limit undesired cellular damage, but this protection might not be complete; hence, the additional foreign resistance in the form of dietary antioxidants will help to cure excessive cellular damage that was caused by excessive formation of ROS [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…and Nelumbo lutea Willd. N. nucifera is distributed in East, South and Southeast Asia and North Australia [ 47 ], with pink or white tepals, whereas N. lutea is found in Central and North America with pale yellow tepals [ 36 ]. In addition, the central disc of N. nucifera leaves is shallowly lobed while that of N. lutea leaves is deeply lobed, an important distinguishing feature between the two species.…”
Section: Introductionmentioning
confidence: 99%